Psychological and Neurobiological Aspects of Eating Disorders A Taste-fMRI Study in Patients Suffering from Anorexia Nervosa - Burkert, Nathalie Tatjana (Springer Fachmedien Wiesbaden : Imprint: Springer, 2016)
This book provides evidence about an altered taste processing due to the administration of a sweet, sour, or umami taste in patients suffering from Anorexia Nervosa (AN). Moreover, the results show for the first time that taste processing is associated with psychological aspects such as stress, anxiety, co-morbidities, or the duration of the illness in AN. Anorexia Nervosa is among the most widely spread and most severe mental diseases in Western countries. In this book the results of several analyses in 21 women suffering from AN compared to 21 healthy control women (CW) are illustrated. The results of this study contribute to a better understanding of the pathophysiology of AN, and, therefore, help to improve the treatment. Contents Psychological Aspects of Anorexia Nervosa Structural Changes Taste Processing Associations between Psychological Symptoms and Neurobiological Aspects Target Groups urers and="" students="" of="" psychology,="" sociology="" medicine Psychologists, Psychotherapists, Physicians, who have to do with Eating Disorders The Author Nathalie Tatjana Burkert is a clinical and health psychologist. Since 2010 she works as a university assistant at the Institute of Social Medicine and Epidemiology at the Medical University of Graz. Her research focuses on eating disorders, weight, nutrition, and associations with health.